Changes in Social Behaviour of Benteng Chinese Community in Organizing Cio Tao Wedding - Saehu, Rahmat (Komunitas, 2018)
Culture resistance in modern era like nowadays is an important thing. In urban communities, culture is increasingly biased with each other so that it is no longer the main thing in everyday life. Cio Tao customary marriage until now still lives in the Benteng Chinese community in Tangerang and the Chinese community in general in Indonesia but is now shifting because of the times and things. This study aims to describe changes in social behavior of the Chinese Benteng community in the implementation of traditional marriage. The method used in this study is Qualitative with an Ethnographic approach. Research location is in Mekarsari Village, Neglasari District, Tangerang City, Banten Province, Indonesia. The informants in this study amounted to eight people consisting of the Benteng Chinese community and related parties involved in it. Data collection techniques in this study are interviews and observations. Data validity uses source validity and methods with Spradley phased forward model analysis techniques. The results showed that changes in social behavior of the Chinese Benteng community in organizing Cio Tao marriages were influenced by several factors including conversion of religion, economic conditions that were less strong and the influence of modernization. These changes are the result of responses to the stimuli they face.